Creation of High-Yielding Winter Wheat Varieties with High Yield and Grain Quality Suitable for Irrigated Conditions. - I. U. Egamov, R. I. Siddikov, T. A. Rakhimov, N. Kh. Yusupov (International Journal of Modern Agriculture, 2021)
One of the most pressing issues today is the creation of varieties and hybrids of winter soft wheat with high grain yields and high quality, suitable for the irrigated conditions of the country, the selection of collection samples for use in the selection process. Therefore, in our research to create new varieties and hybrids of winter soft wheat and to carry out selection work to test them at all stages of the selection process. In order to achieve this goal, hybridization was carried out using varieties and samples of world winter soft wheat, Uzbekistan-25, Navbahor, Yogdu, Aziz varieties of winter wheat were created and the primary seed system was widely introduced into production.